Bridging hydraulic diffusivity from aquifer to particle-size scale: a study on loess sediments from southwest Hungary - Pacheco, F. A. L.; Landim, P. M. B. [UNESP]; Szocs, Teodora (Taylor &Francis Ltd, 2015)
In situ megascale hydraulic diffusivities (D) of a confined loess aquifer were estimated at various scales (10 <= L <= 1500 m) by a finite difference model, and laboratory microscale diffusivities of a loess sample by empirical formulas. A scatter plot reveals that D fits to a single power function of L, providing that microscale diffusivities are assigned to L = 1 m and that differences in diffusivity observed between micro- and megascales are assigned to medium heterogeneity appraised by variations in the curvature and slope of natural hydraulic head waves propagating through the aquifer. Subsequently, a general power relationship between D and L is defined where the base and exponent terms stand for the aquifer storage capability under a confined regime of flow, for the microscale hydraulic conductivity and specific yield of loess, and for the changes in curvature and slope of hydraulic head waves relative to values defined at unit scale.[GRAPHICS]Editor Z.W. Kundzewicz
Keywords: Hydraulic diffusivity; Ioess; Hydraulic head wave; Grain-size distribution; Confined aquifer; Scale